YOUTH ENTREPRENEURIAL DEVELOPMENT THROUGH CREATIVE PRODUCT BRANDING WORKSHOPS - Friend Zakharia; Heriyanto Heriyanto; Ajeng Faizah Nijma Ilma (JOURNAL OF COMMUNITY DEDICATION, 2025)
Youth entrepreneurship development is a crucial strategy for fostering economic independence and creating new jobs amidst increasingly complex global challenges. This community service program, titled "Youth Entrepreneurial Development through Creative Product Branding Workshops," aims to provide a conceptual and practical foundation for supporting the capacity building of young entrepreneurs through creative product branding training. Using a literature review method, this study summarizes previous findings regarding the effectiveness of workshops as participatory learning tools and the importance of branding strategies in enhancing the competitiveness of fledgling MSME products. The study's findings demonstrate that collaboratively and contextually designed training fosters an innovative entrepreneurial mindset, enhances visual communication skills, and strengthens product identity in the marketplace. These findings serve as the basis for designing a community service program model that is applicable and relevant to the needs of young entrepreneurs in the digital economy era.